The Designing of a Digital Book on the History of Rubber Plantation Based on the Experiential Learning Model as a Trigger for Learning History Meaning Entrepreneurship - Monalisa monalisa; Muhammad Akhyar; Musa Pelu (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: To achieve the level of prosperity is not an easy thing. Becoming an entrepreneur is not an alternative profession, but being an entrepreneur is a strategic choice that must be made with a firm and strong determination.